TRIBAL SOCIETY IN CONTEMPORARY HINDI NOVELS : STRUGGLES, ISSUES AND SOCIAL REALITY - Anitha.P.L (ShodhKosh: Journal of Visual and Performing Arts, 2023)
With social change and development, it has also been observed that the progress of every society impacts all its sections. In Indian society, the tribal community is one that continues to struggle to protect its identity and resources. This struggle is not only economic but also social, cultural, and political. Serious questions are still being raised about the extent to which various developmental changes have affected the tribal community. Issues such as casteism, exploitation, and social discrimination persist in tribal society, and these challenges are effectively depicted in contemporary literature and novels.